The merit of superimposed vibration for flexibility and passive stiffness: A systematic review with multilevel meta-analysis - Jochum D; Konrad A; Lohmann LH; Cochrane D; Rittweger J; Vogel V; Warneke K (Elsevier B V on behalf of Shanghai University of Sport, 2025)
Background: Due to its high relevance in sports and rehabilitation, the exploration of interventions to further optimize flexibility becomes paramount. While stretching might be the most common way to enhance range of motion, these increases could be optimized by imposing an additional activation of the muscle, such as mechanical vibratory stimulation. While several original articles provide promising findings, contradictory results on flexibility and underlying mechanisms (e.g., stiffness), reasonable effect size (ES) pooling remains scarce. With this work we systematically reviewed the available literature to explore the possibility of potentiating flexibility, stiffness, and passive torque adaptations by superimposing mechanical vibration stimulation. Methods: A systematic search of 4 databases (Web of Science, MEDLINE, Scopus, and Cochrane Public Library) was conducted until December 2023 to identify studies comparing mechanical vibratory interventions with passive controls or the same intervention without vibration (sham) on range of motion and passive muscle stiffness in acute (immediate effects after single session) and chronic conditions (multiple sessions over a period of time). ES pooling was conducted using robust variance estimation via R to account for multiple study outcomes. Potential moderators of effects were analyzed using meta regression. Results: Overall, 65 studies (acute: 1162 participants, chronic: 788 participants) were included. There was moderate certainty of evidence for acute flexibility (ES = 0.71, p < 0.001) and stiffness (ES = –0.89, p = 0.006) effects of mechanical vibration treatments vs. passive controls without meaningful results against the sham condition (flexibility: ES = 0.20, p < 0.001; stiffness: ES = –0.19, p = 0.076). Similarly, moderate certainty of evidence was found for chronic vibration effects on flexibility (control: ES = 0.64, p = 0.043; sham: ES = 0.65, p < 0.001). Lack of studies and large outcome heterogeneity prevented ES pooling for underlying mechanisms. Conclusion: Vibration improved flexibility in acute and chronic interventions compared to the stand-alone intervention, which can possibly be attributed to an accumulated mechanical stimulus through vibration. However, studies on biological mechanisms are needed to explain flexibility and stiffness effects in response to specific vibration modalities and timing.
Keywords: Whole-body vibration; Stretching; Foam rolling; Range of motion; Muscle stiffness